High-Performance Work System, Strategic Flexibility, and Organizational Performance—The Moderating Role of Social Networks - Wang, Yizhi; Cao, Yi; Xi, Nan; Chen, Huitian (Frontiers in Psychology, 2021)
Based on the dynamic capability theory. This research investigated the effect of high-performance work system on organizational performance. From the sociological perspective, this research also tested the mediating role of strategic flexibility and the moderating role of enterprise’s social network between high-performance work system and organizational performance. A total of 214 middle and senior managers from 58 Chinese enterprises were invited to participate this research. The results showed that the high-performance work system is positively correlated with organizational performance and such correlation is (partially) mediated by strategic flexibility. It is also found that the enterprise’s social network negatively moderated the relationship between high-performance work system and strategic flexibility. However, social network did not moderate the mediating role of strategic flexibility in high-performance work system and organizational performance. These results can contribute a theoretical reference for the management of Chinese enterprises.